Bulacan historical and exposition complex - Quiambao, Michael Collins P. (Manila : National University, 2000)
Historical and Exposition Complex, the place were researchers, tourist, antique lovers, explorers could easily adapt. It is the place of the world of the past, having a flashback of what has been developed to attain the progress of the future. Museums are veritable repositories of a nations cultural heritage. It offers nourishment not only for the eyes but also for the soul. A visit Into a historical museum can be a poignant and culturally- rewarding experience. You get to see a different world- A world of color and light, lines, shape and shadow. But most of all, the museums give you the chance to travel back in time.